Foliar salicylic acid application to enhance the morphophysiology of Basella alba and Basella alba var. cordifolia under water deficit stress - ANNIS WATURROIDAH AYUNINGTIAS; SOLICHATUN SOLICHATUN; ARTINI PANGASTUTI (Nusantara Bioscience, 2024)
Abstract. Ayuningtias AW, Solichatun, Pangastuti A. 2024. Foliar salicylic acid application to enhance the morphophysiology of Basella alba and Basella alba var. cordifolia under water deficit stress. Nusantara Bioscience 16: 96-103. Global climate change and increasing temperatures are becoming problems in the cultivation of medicinal plants such as Basella alba L. and Basella alba var. cordifolia (Lam.) M.R.Almeida. Foliar salicylic acid on leaves increases growth and productivity in medicinal cultivation. This study aims to determine the exogenous application of salicylic acid to increase the morphophysiology measurement in B. alba and B. alba var. cordifolia under water deficit stress. The study was carried out using a two-factor, completely randomized design consisting of salicylic acid concentration (0, 2, and 6 mM) and water deficit stress (100% (control), 75% field capacity (light stress), 50% wide field capacity (medium stress) and 25% field capacity (heavy stress). The observation results included morphophysiology. The best result on dry weight for B. alba was followed by SA 0mM+Medium stress with 5.45 g; in B. alba var. cordifolia was followed by SA 0mM+ Heavy stress with 3.09 g. Fresh weight for B. alba was followed by SA 4mM+ Heavy stress with 35.95 g, and B. alba var. cordifolia was followed by SA 0mM+ Heavy stress with 35.66 g. The shoot-to-root ratios in B. alba and B. alba var. cordifolia were followed by SA 2mM+Medium stress with 0.93 and 0.99, respectively. Quercetin in B. alba was followed by SA 4mM+ Heavy stress with 2.88% w/w, and B. alba var. cordifolia was followed by SA 6mM+Medium stress with 1.93% w/w. The gallic acid in B. alba and B. alba var. cordifolia was followed by SA 6mM+Medium stress with 10.21% w/w and 9.44% w/w. Prolin in B. alba and B. alba var. cordifolia was followed by SA 6mM+Medium stress with 8.74 and 9.73 µmol/gram wet weight. This study concluded that foliar salicylic acid application enhanced the morphophysiology, including growth, secondary metabolites, and proline accumulation of B. alba and B. alba var. cordifolia under water deficit stress.